2005
DOI: 10.1590/s0004-27492005000300014
|View full text |Cite
|
Sign up to set email alerts
|

Análise laboratorial das ceratites infecciosas secundárias à cirurgia refrativa

Abstract: The agreement between culture and smear results was 80.2%; regarding the type of surgery there was no statistically significant relationship between time of onset of infection and surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(36 reference statements)
0
2
0
2
Order By: Relevance
“…No patient with mycobacterial infection was detected. Our results were in accordance with the previous two largest series of post-PRK keratitis, indicating that Gram-positive microorganisms were responsible in almost all cases [18,19]. Therefore, it seems that Gram-positive organisms posed the greatest risk of infectious keratitis after PRK surgery and, due to the remarkable ocular morbidity associated with infectious keratitis, we strongly recommend the use of prophylactic antibiotics after PRK.…”
Section: Discussionsupporting
confidence: 91%
“…No patient with mycobacterial infection was detected. Our results were in accordance with the previous two largest series of post-PRK keratitis, indicating that Gram-positive microorganisms were responsible in almost all cases [18,19]. Therefore, it seems that Gram-positive organisms posed the greatest risk of infectious keratitis after PRK surgery and, due to the remarkable ocular morbidity associated with infectious keratitis, we strongly recommend the use of prophylactic antibiotics after PRK.…”
Section: Discussionsupporting
confidence: 91%
“…In a previous literature review, 11 anecdotal cases of infectious keratitis after PRK caused by mycobacteria and fungi were identified; however, in the 2 largest series of keratitis after PRK, grampositive microorganisms were responsible for all cases 11 or for all cases except 1 (caused by fungus). 12 Donnenfeld et al 11 registered a single case caused by a gramnegative microorganism, Pseudomonas aeruginosa. A high incidence of bacterial keratitis caused by P aeruginosa has been reported in studies of contact lens-related keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…A 2003 literature review by Donnenfeld et al 11 identified 26 reported cases of bacterial keratitis after PRK, although no statistical evaluation was performed. In a study by Leal et al, 12 only results from cultures or scrapings were provided and there was no information about presentation characteristics, management, or visual outcomes.…”
mentioning
confidence: 99%
“…Diversos estudos nacionais (1)(2)11) e internacionais (3)(4)(5)(6)(7)(8)(9)(12)(13)(14)(15)(16)(17) foram realizados, buscando avaliar não somente a etiologia como também a eficácia clínica e a atividade de diferentes antimicrobianos para as doenças oculares, ressaltando como agentes os Staphylococcus ssp. Em 1998, foi demonstrada resistência aumentada à gentamicina e meticilina (9) , e neste mesmo ano, outra pesquisa concluiu que as fluoroquinolonas eram superiores aos aminoglicosídeos no tratamento das infecções oculares pelo SCoN, estudando a suscetibilidade antimicrobiana de amostras oculares isoladas em 12 laboratórios da América do Norte e América do Sul (3) .…”
Section: Discussionunclassified